PRA RANCANG BANGUN BRIKET CANGKANG BIJI KARET DENGAN KAPASITAS 8.900 Ton/Tahun - Nilasari, Umi Ratna; Abrina Anggraini, Sinar Perbawani; Iskandar, Taufik (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
The necessity of energy become a priority by goverment at this time, because the final consumtion of national energy on 2000-2012 increases 2,9% for each year. By using the fossil energy continuesly that can make the availibility of energy become rare, there are so many policy that created by goverment to control this problem, one of this using the policy is alternative energy. The alternative energy can get from some resources and products such as water energy, wind, geothermal, biodiesel, and biomass. Briquettes is a pottential fuel and very relieble as alternative energy for household needs and able to supply and a long time. Pre-design planning of rubber seed shell briquettes is using slow pyrolysis system. Where, the shell heated in 350Âº C - 400Âº C in 1 atm pressure for 6 hours process. The pre-design planning will build in Landak district of West Borneo. Pre-design planning of rubber seed shell briquettes that using slow pyrolysis system will build on 2020 with 8.900 ton/year capacity. The process is raw material preparation, pyrolysis reaction, separation and purificatin, and product handling. Based on economic analysis this plant feasible to set based on the economic aspects as follows : ROIAT(%) : 75,7%, POT(tahun) : 1,2 , BEP (%) : 37%, IRR(%) : 19,47. Key word : energy, briquettes, slow pyrolysis